Histological Study of Discoid Lateral Meniscus in Children and Adolescents: Morphogenetic Considerations - Tudisco, Cosimo; Botti, Flavia; Bisicchia, Salvatore (Joints, 2019)
Background Discoid lateral meniscus is the most frequent variant of the meniscus. Few studies have focused on the histology of discoid menisci. The aim of the present study was to report the histological findings of discoid lateral meniscus in children and adolescents, after arthroscopic partial resection, to give a possible explanation of its developmental etiology.Methods Five patients aged 9, 10, 13, 15, and 17 years were operated on for a 1-piece excision of a discoid lateral meniscus, and the specimens were histologically examined.Results The extracellular matrix showed a different distribution and characteristics depending on the different side of the meniscus. Irregularly oriented collagen fibers in discoid lateral meniscus were found. Cells of different shapes were observed depending on the surficial or deep location in the tissue. There were no blood vessels in the inner part of discoid lateral meniscus.Conclusion The findings of the current study seem to confirm that discoid lateral meniscus arises from variant morphogenesis. Furthermore, the altered distribution and shape of the cells and disorganization of collagen fibers (irrespectively of the age of the patients) may predispose discoid lateral meniscus to degeneration, damage, and tear in young patients also.Level of Evidence Level of evidence 4 (case series).
Keywords: discoid lateral meniscus; histology; children; knee; development